New aggregation-induced emitters: tetraphenyldistyrylbenzenes - Freudenberg, Jan; Rominger, Frank; Bunz, Uwe H. F. (Chemistry - a European journal, 2015)
Abstract The synthesis of five novel distyrylbenzene (DSB) derivatives, featuring a central tetraphenylbenzene core, is reported. The targets show aggregation-induced emission (AIE), which, however, is substituent-dependent. For the pure hydrocarbon and derivatives that do not carry (+M) or (?M) substituents, classic AIE behavior is observed, that is, the DSBs are non-fluorescent in solution, but are highly fluorescent in cold matrices, upon aggregate formation in poor solvents and in the solid, crystalline state. If aldehyde or dibutylamino groups are attached in the para-position of the DSB unit, non-classic AIE-phores result. These are fluorescent both in dilute solution as well as in the solid state. Prolonged irradiation of the targets leads to benzotetraphene derivatives by a double cyclization.
Gesehen am 01.07.2020